Curriculum framework for preparing quality teachers for the future: developing guiding principles - Ratnavadivel Nagendralingan, Chang Lee Hoon, Salih Maria, Low Jeffery, Karuppiah Nagalingam, Omar Ainon, Md. Yassin Sopia, Dawi Amir Hasan, Saad Noor (N/A, 2014)
Curriculum framework for preparing quality teachers for the future: developing guiding principles by Ratnavadivel Nagendralingan, Chang Lee Hoon, Salih Maria, Low Jeffery, Karuppiah Nagalingam, Omar Ainon, Md. Yassin Sopia, Dawi Amir Hasan, Saad Noor